Pengaruh Sistem Pelayanan, Ketepatan Waktu dan Daya Beli Masyarakat terhadap Loyalitas Menggunakan Jasa Transportasi Bus pada PT. Atlas - Monalisa Tampubolon; Miftahul Jannah; Rinaldi Gultom; Hendra Jonathan Sibarani (Journal of Education, Humaniora and Social Sciences (JEHSS), 2020)
This study was conducted to determine the effect of service system, timeliness and power of buying community against to loyalty using bus transportation services in PT. Atlas.   The method used in this study uses a quantitative approach and uses explanatory research characteristics. Based on the population in this study, the customer for the ticket purchasing service was 778 people. The sampling technique used the Slovin formula as many as 89 people used in this study. Based on the results obtained from this study using partially obtained the value of the service system has a tcount of 6,106> 1,988, punctuality has a tcount of 1,299 <ttable 1,988, while purchasing power has a tcount of 0.043 <ttable 1.988 which means punctuality and purchasing power has no positive and significant effect on service user loyalty at PT. ATLAS Medan, while simultaneously the value of Fcount is (13.451)> Ftable of (3.10) with a sig value of 0.000 <0.05, which means that the service system, timeliness and purchasing power of the community have a positive and significant effect on the loyalty of transportation service users.